The growing number of hemophilia registries: Quantity vs. quality. Issue 5 (3rd April 2015) - Keipert, C; Hesse, J; Haschberger, B; Heiden, M; Seitz, R; van den Berg, HM; Hilger, A; on behalf of the ABIRISK Consortium
<x xml:space="preserve">Abstract</x> Registries for rare diseases provide a tool for obtaining an overview of the clinical situation and can be used to discover points of improvement and to monitor long‐term safety. Registries could also become a powerful tool to provide supporting information for marketing authorization. There is an urgent need for a pan‐European or global strategy that supports consistent data. Therefore, transparency in data collection, harmonization of the database structures, and the convergence of scientific approaches are required.